2021
DOI: 10.1097/upj.0000000000000233
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Urology Residency Program Directors Assessing Criteria to Interview Applicants during the COVID-19 Pandemic

Abstract: Introduction:We aimed to determine criteria of interest to urology residency program directors when selecting applicants for residency interviews during the COVID-19 pandemic.Methods: An anonymous survey was sent via email to all urology residency program directors across the United States. Program directors were asked to assign the degree of importance (1e5, with 5 being very important) of selected factors in deciding which applicants to interview. Surveys were distributed and study data were managed using RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…A recent survey of Urology program directors on interview criteria during the COVID-19 pandemic also showed that 54.7% rank the student's visa status as very important, second only to Urology letters of recommendation (64.1%). 18 Our survey also indicated most students rarely felt comfortable tweeting/retweeting about racial, political, and diversity issues. Prior studies demonstrated African-American and Hispanic populations are underrepresented in the general field of Urology as well as academic leadership roles for Urology.…”
Section: Discussionmentioning
confidence: 82%
“…A recent survey of Urology program directors on interview criteria during the COVID-19 pandemic also showed that 54.7% rank the student's visa status as very important, second only to Urology letters of recommendation (64.1%). 18 Our survey also indicated most students rarely felt comfortable tweeting/retweeting about racial, political, and diversity issues. Prior studies demonstrated African-American and Hispanic populations are underrepresented in the general field of Urology as well as academic leadership roles for Urology.…”
Section: Discussionmentioning
confidence: 82%
“…Another theme shared by the studies was that program directors did not consider SoMe to be an important aspect of evaluating applicants (10,13,15). This contrasts current applicant beliefs, as over 30% felt that program directors were evaluating their SoMe use during the application cycle (15).…”
Section: Discussionmentioning
confidence: 97%
“…The other study found that only 6% of program directors reviewed an applicant's SoMe before offering an interview (10). Furthermore, greater than 80% of program directors reported that SoMe played no role in assessment of applicants (10,13). Even though only a small proportion of program directors acknowledged SoMe was considered in the application process, one survey found that 15% of program directors reported SoMe was beneficial to an applicant's chances of matching and 12% reported that SoMe hurt an applicant's chances (13).…”
Section: Influence Of Social Media On the Urology Match Processmentioning
confidence: 96%
See 2 more Smart Citations